TERRORISM OF OUR DAYS: GLOBAL AND REGIONAL MANIFESTATIONS - AKAEV, Vakhit; KELIGOV, Murad; NANAEVA, Boryat (CENTRAL ASIA AND THE CAUCASUS, 2017)
Today, terrorism has developed into a highly specific phenomenon, the content of which and the conditions in which it was taking shape are fairly complicated. It figures prominently in domestic and foreign policies of certain states and international organizations. It is rooted in hoary antiquity, yet its various manifestations are characteristic of our days as well. The global, political, and ideological processes unfolding in the world are accompanied by international terrorism in different forms and carried out under specific ethnic or religious slogans. We have analyzed Islamism and “Islamic” terrorism, and their radical or extremist manifestations camouflaged as Islamic values.